Education for a Digital World Advice, Guidelines and Effective Practice from Around Globe - Hirtz, Sandy; Harper, David G. (Open textbook library., 2008)
Education for a Digital World contains a comprehensive collection of proven strategies and tools for effective online teaching, based on the principles of learning as a social process. It offers practical, contemporary guidance to support e-learning decision-making, instructional choices, as well as program and course planning, and development.Practical advice, real-life examples, case studies, and useful resources supply in-depth perspectives about structuring and fostering socially engaging learning in an online environment. A plethora of e-learning topics provide insights, ideas, and usable tools. Tips and evidence-based theory guide administrators, program and course developers, project teams, and teachers through the development of online learning opportunities.Education for a Digital World is an indispensable guide, resource, textbook and manual for policymakers and practitioners in developing and developed countries.